Residual stress management in welding: measurement, fatigue analysis and improvement treatments - Kudryavtsev, Yu.; Kleiman, J. (Автоматическая сварка, 2013)
Residual stress (RS) management is a concept according to which three major stages, i.e. RS determination, RS fatigue analysis
and RS beneficial redistribution are considered and evaluated, either experimentally or theoretically to achieve the optimum
performance of welded structures. All three stages as well as a number of new engineering tools such as ultrasonic computerized
complex for residual stress measurement, UltraMARS, software for analysis of the effect of residual stresses on the fatigue life of
welded elements, ReSIsT, and new technology and, based on it, compact system for beneficial redistribution of residual stresses
by ultrasonic impact treatment, UltraPeen, will be discussed. Examples of industrial applications of the developed engineering
tools for residual stress analysis and fatigue life improvement of welded elements and structures will be given.